Beneficial effects through aggressive coronary screening for type 2 diabetes patients with advanced vascular complications. Issue 33 (August 2016) - Tsujimoto, Tetsuro; Sugiyama, Takehiro; Yamamoto-Honda, Ritsuko; Kishimoto, Miyako; Noto, Hiroshi; Morooka, Miyako; Kubota, Kazuo; Kamimura, Munehiro; Hara, Hisao; Kajio, Hiroshi; Kakei, Masafumi; Noda, Mitsuhiko
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Glycemic control alone does not reduce cardiovascular events in patients with type 2 diabetes (T2D), and routine screening of all T2D patients for asymptomatic coronary artery disease (CAD) is not effective for preventing acute cardiac events. We examined the effectiveness of an aggressive screening protocol for asymptomatic CAD in T2D patients with advanced vascular complications. We designed a 3-year cohort study investigating the effectiveness of the aggressive coronary screening for T2D patients with advanced vascular complications and no known coronary events using propensity score adjusted analysis at a national center in Japan. Eligibility criteria included T2D without known coronary events and with any 1 of the following 4 complications: advanced diabetic retinopathy, advanced chronic kidney disease, peripheral artery disease, or cerebrovascular disease. In the aggressive screening group (n = 122), all patients received stress single photon emission computed tomography and those exhibiting myocardial perfusion abnormalities underwent coronary angiography. In the conventional screening group (n = 108), patients were examined for CAD at the discretion of their medical providers. Primary endpoint was composite outcome of cardiovascular death and nonfatal cardiovascular events. Asymptomatic CAD with ≥70% stenosis was detected in 39.3% of patients completing aggressive screening. The proportions achieving revascularization and receiving intensive medical therapy within 90 days after the screening were significantly higher in the aggressive screening group than in the conventional screening group [19.7% vs 0% ( P < 0.001) and 48.4% vs 9.3% ( P < 0.001), respectively]. The cumulative rate of primary composite outcome was significantly lower in the aggressive screening group according to a propensity score adjusted Cox proportional hazards model (hazard ratio, 0.35; 95% confidence interval, 0.12–0.96; P = 0.04). Aggressive coronary screening for T2D patients with advanced vascular complications reduced cardiovascular death and nonfatal cardiovascular events.